2007
DOI: 10.1080/09712119.2007.9706840
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Gross Chemical Compositions of Ewe and Goat Colostrum During Ten Days Postpartum

Abstract: Keskin, M., Guler, Z., Gul, S. and BiCer, 0. 2007

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…In the study of changes in colostrum and ewes' (Würtemberg breed) milk composition, Antunovi c, Steiner, Sen ci c, Mandi c, and Klapec (2001) found the highest milk fat content on the 2nd day of lactation followed by a decrease on the 10th and 30th day of lactation, and an increase on the 60th day of lactation in the winter as well as in the summer feeding season. To determine the exact colostrum producing period in Awassi ewes, Keskin, Güler, Gül, and Biçer (2007) studied the daily changes in milk fat contents for ten days after parturition. The authors found the highest fat content (w10%) on the first day postpartum, while that on the 10th day decreased to w7%.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of changes in colostrum and ewes' (Würtemberg breed) milk composition, Antunovi c, Steiner, Sen ci c, Mandi c, and Klapec (2001) found the highest milk fat content on the 2nd day of lactation followed by a decrease on the 10th and 30th day of lactation, and an increase on the 60th day of lactation in the winter as well as in the summer feeding season. To determine the exact colostrum producing period in Awassi ewes, Keskin, Güler, Gül, and Biçer (2007) studied the daily changes in milk fat contents for ten days after parturition. The authors found the highest fat content (w10%) on the first day postpartum, while that on the 10th day decreased to w7%.…”
Section: Introductionmentioning
confidence: 99%
“…Sheep farming activity, which is an important part of animal production activities worldwide, is of great importance both economically and in terms of human health in Türkiye as well. Especially in the Central and Eastern Anatolia Region, sheep farming is quite common, and the climate and pasture structure in this region make sheep farming an important source of income (Keskin et al, 2007;Özyürek, 2017;Türkyılmaz et al, 2021). Throughout history, sheep have played an important role in the economic and social life of Turkish communities both in nomadic migrations from Central Asia to Anatolia and in settled life (Özbey & Akcan, 2000;Biçer et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In goats, colostrum composition has been investigated since 1840 in different breeds worldwide [12]. Studies have characterized the colostrum of German, Swiss [13,14], Spanish [15][16][17][18], and cosmopolitan breeds [19][20][21]. On the other hand, Italian breeds have been neglected.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of colostrum may depend on various factors. Parity and litter size could influence it, but findings are still controversial [13][14][15][16][17][18][19]21,24,31], while regarding the farming system, studies have been carried out only in cattle [32]. Moreover, variations in the colostrum composition occur not only according to the species, but also to the breed, and, to our knowledge, there is no information concerning the local breeds of Northern Italy.…”
Section: Introductionmentioning
confidence: 99%